SISTEM INFORMASI TOKO ONLINE BRANDAL DENIM - , SAKRAL ADAM ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Brandal denim is a store which is selling various kinds of clothes. The information system of Brandal denim Online Shop is needed for it will ease the data processing process, organizing the customersâ order and in its effort to expand the market. This was the result of the competition between each store with a same product and also the store management system still use a book to note every buying and selling activities so it will be hard to check the development report for some certain period of time. This system was based on web using PHP programming language together with CodeIgniter as the framework, Javascript with jquery as the framework, and MySQL for its database management. The system can be used to manage some data item like categories, product, ordering product, and customer. It also provides the user with its feature to make report, for example, the profit gained in certain period of time.